Synthesizing Pesantren Traditions and Digital Pedagogies: Strategies and Evaluation of Character-Based Islamic Religious Education Innovation in Vocational Schooling - Laili, Nur; Achadi, Muh. Wasith; Sholihah, Alfiani Rif'atus (Fakultas Ilmu Tarbiyah dan Keguruan Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2026)
This study investigates the strategies, evaluation mechanisms, and developmental recommendations for character-based Islamic Religious Education (IRE) curriculum innovation at SMK Aswaja Banyuwangi. Employing a descriptive qualitative approach with a single case study design, the research explores how vocational frameworks systematically integrate spiritual traditions with modern educational demands. Data were collected through semi-structured interviews with key informants, field observations, and documentation reviews, followed by thematic analysis and rigorous triangulation to ensure internal validity. Results indicate that curriculum innovation is driven by a comprehensive need analysis aimed at aligning learning with contemporary dynamics while maintaining holistic character building. The implementation utilizes student-centered models, specifically Project-Based Learning (PjBL) and Problem-Based Learning (PBL) supported by digital platforms like Canva and Quizizz, which effectively foster creativity, critical thinking, and religious discipline. Furthermore, the evaluation framework shifts from conventional testing to a continuous, comprehensive system incorporating worship monitoring journals and behavioral rubrics. The findings imply that a synergy between institutional leadership and pedagogical technology can successfully unify vocational competence with Islamic spiritual values. However, the study is limited by its specific case scope and a restricted participant pool, necessitating caution regarding broader generalizability. Consequently, future research should focus on longitudinal assessments of character outcomes and the diversification of AI-supported tools to mitigate teacher adaptation fatigue in rapidly changing policy environments.